Spatio-temporal variation of the density of shrimps Farfantepenaeus subtilis, Litopenaeus schmitti and Xiphopenaeus kroyeri (Crustacea; Decapoda) in the Curuçá Estuary, North of Brazil - Antonio Sérgio Silva de CARVALHO; Jussara Moretto MARTINELLI-LEMOS; Andréia Barbosa das NEVIS; Victoria ISAAC (Boletim do Instituto de Pesca)
The shrimps Penaeidae represent one of the most frequent and exploited fishery resources in coastal regions worldwide. In the estuaries of the north coast of Brazil they are caught, even when juveniles, by artisanal fisheries and mostly serving local markets. The objective of this study was to determine the composition, abundance and spatio-temporal distribution of species of Penaeidae shrimp caught in the Curuçá estuary, State of Pará, north coast of Brazil. The samples were collected every two months from July 2003 to July 2004 in eight sampling sites using an otter trawl net when the tide was ebbing. Two profiles were selected to study this area: Muriá tidal creek and the Curuçá River, with four sampling points in each site. A total of 6,158 Penaeidae shrimps, belonging to three species, were obtained. Farfantepenaeus subtilis was the dominant species with 78.5% of the total of shrimps, followed by Litopenaeus schmitti and Xiphopenaeus kroyeri that corresponded to 11.5 and 9.8%, respectively. The highest density of F. subtilis and X. kroyeri was obtained during the rainy season (p <0.05), with a density of 197.4 ind./1,000 m2 and 23.7 ind./1,000 m2 respectively, both in March/04. The white shrimp (L. schmitti) was more abundant in the dry season and had two peaks of larger density in July 2003 (10.4 individuals/1,000 m2), dry season and one second peak in March (16.5 individuals/1,000 m2), rainy season. These results show the importance of the Curuçá estuary for the life cycle and maintenance of coastal stocks of these species.